2017
DOI: 10.18203/2349-3291.ijcp20170536
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal mortality of sick newborns admitted in a tertiary care teaching hospital in Tamil Nadu, South India

Abstract: Background: Neonatal period is an important period in the life where most of the deaths are preventable. In India every year 1 million babies die, which contributes to 25% of the world neonatal mortality. Perinatal death is very high in developing countries including India.Methods: A record based retrospective study was conducted in the Neonatal Intensive care unit(NICU) of Department of Pediatrics, Chengalpattu Medical College in Tamil Nadu, South India. The records were collected for the period of one year f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
3
3
0
Order By: Relevance
“…Similarly association of positive outcome with higher birth weight was noted in numerous studies. (11,20,26,29,32,33,34,35,36,37,38,39) In accordance to current study many other researches also concluded a successful outcome associated with higher gestational age. (28,29,32,34,35,37,39).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similarly association of positive outcome with higher birth weight was noted in numerous studies. (11,20,26,29,32,33,34,35,36,37,38,39) In accordance to current study many other researches also concluded a successful outcome associated with higher gestational age. (28,29,32,34,35,37,39).…”
Section: Discussionsupporting
confidence: 90%
“…(11,20,26,29,32,33,34,35,36,37,38,39) In accordance to current study many other researches also concluded a successful outcome associated with higher gestational age. (28,29,32,34,35,37,39). In congruence with our study Garg P et al (2005) (p=0.0001) also observed longer duration of stay associated with favourable outcome.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Use of government ambulance for referral was higher than what was observed by another hospital in Delhi. 6 Newborn transport in a wellequipped ambulance could play a vital role in reducing death during transport. A relevant point in this regard is prior communication to NICU/SNCU.…”
Section: Discussionmentioning
confidence: 99%
“…NMR accounts for >50% of IMR and a small gain in this domain has a huge impact on overall quality of life (QoL) [7]. All published studies to date reporting NMR and morbidity statistics are from tertiary care centers and teaching hospitals that may not necessarily reflect ground realities of rural and semi-urban areas [8][9][10]. Increasingly SNCU and neonatal intensive care unit (NICU) are established as a public-private partnership (PPP) initiative between government health authorities and non-governmental organizations (NGO) bringing secondary/tertiary care services to area of need [11].…”
Section: Introductionmentioning
confidence: 99%